PENYAJIAN BERITA SEBAGAI UPAYA PENCEGAHAN PENYALAHGUNAAN NARKOBA (Lembaga Penerbitan Universitas Esa Unggul, 2018)
AbstractAlready 15 years National Narcotics Agency (BNN) stands, but the duty of prevention of narcotics abuse has not been successful. This condition demands the participation of the community, including journalists to make efforts to prevent against drug abuse. This research tries to analyze how to make news presentation by journalist can serve as an effort to prevent against drug abuse. The authors use case study research designs by observing the news about drugs and interviewing various informants related to the news about drugs. The results show, news about drugs has been loaded by many journalists, but most news about the prosecution, because the facts about the act of having a higher value of news than the facts about prevention. Journalists have no guidance in presenting the news about drugs, so the facts about drugs are treated like other facts. While Indonesia is in a state of